(untitled) (ELang | An English Language Education Journal, 2021)
The researcher investigated “Improving Students’ Listening Skill by Using Breaking News Video” to the second grade MA Yamisa Soreang students in 2020/2021 academic year. The aims of the research are to know whether breaking news video effective to teach listening to the second grade students, and also to know how the students response after taught by using breaking news video as the media. A pre-experimental design used to conduct this research. The population of this research is the second grade students of MA Yamisa Soreang. The sample of this study is 19 students. To get the data, the researcher gave the students tests, those were pretest and posttest. The pretest used to know how good the listening skill of the students before the treatment given. The posttest used to know the students listening skill score after the treatment given. After get the data, the researcher counted and analyzed with t-test formula. It is used to determine whether there was a significant different in students score before and after the treatment using breaking news video. The research finding showed that breaking news video is effective to improving students listening skill. It can be seen from the result of the research. The obtained t-test is 4.31 whereas the t-table is 2.101, the t-test value is bigger than the t-table (4.31>2.101). Based on the result, it means that the use of breaking news video as the media to improving students listening skill in the second grade students of MA Yamisa Soreang is effective. Furthermore, based on the questionnaire result, most of the students like being taught by using breaking news video and most of the students agree that breaking news video were useful.